Ruminant digestive physiology as research subject at the Instituto de Ciencia Animal for fifty years - Gutiérrez, Odilia (Cuban Journal of Agricultural Science, 2016)
The Instituto de Ciencia Animal was created in 1965, with the objective of contributing to the development of Cuban cattle rearing under scientific and technical basis and different species of ruminants and non-ruminants were introduced in Cuba and constituted the subject for many researches. The objective of this paper is to report the main results on studies of ruminant digestive physiology after five decades, using the Cuban Journal of Agricultural Science as the main information source. Key words: physiology, digestion, ruminants